A Relationship Between Gender Diversity and Transparency & Disclosure : Case of Fortune 500 Companies - Waiganjo, Lina Njoki (2017)
This research study assesses the relationship between financial transparency and board gender diversity. In the wake of financial scandals, this study highlights the importance of quality financial disclosures and utmost transparency in the corporate world and forms inferences that support the need for gender diversity for the better good of investors. A transparency and disclosure (T&D) index over a six-year period between 2010 - 2015 has been constructed, using proxies relating to financial reporting and board characteristics. The findings are consistent with prior research, that is, there is a significant relationship between a firm’s transparency and disclosure level and the board characteristics, but a negative relationship to firm size. The purpose of this research is for purposes of increased implementation in order to mitigate agency problems and breach of interest with regard to information asymmetry that has so far been the cause of major corporate scandals.